2022
DOI: 10.1111/jan.15366
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and leading a cross‐institutional partnership to integrate fundamentals of care into clinical practice, nursing education and research

Abstract: Aim The aim was to describe and discuss the process of establishing and leading a cross‐institutional partnership to regain focus on and reconceptualize fundamental nursing care in clinical practice, nursing education and research in one region in Denmark. Design A discursive paper. The case study method is used as an adapted frame for describing and discussing the establishment and strategic decisions of a cross‐institutional partnership. Data sources This discursive paper draws on the authors' experiences wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In order to save the patient's life, during the rescue process, medical staff must use instruments for treatment, which leads to different degrees of pain, and nursing staff can relax the patient and reduce pain by taking effective nursing measures based on close detection of the patient's vital indicators. A clean and comfortable hospital environment also belongs to an important measure in nursing care, which can relieve patients' anxiety and help them recover better [ 14 17 ]. In this study, it was shown that the adverse emotions in the observation group were lower than those in the control group, which indicated that standardized care could effectively reduce the adverse emotions of patients and was effective.…”
Section: Discussionmentioning
confidence: 99%
“…In order to save the patient's life, during the rescue process, medical staff must use instruments for treatment, which leads to different degrees of pain, and nursing staff can relax the patient and reduce pain by taking effective nursing measures based on close detection of the patient's vital indicators. A clean and comfortable hospital environment also belongs to an important measure in nursing care, which can relieve patients' anxiety and help them recover better [ 14 17 ]. In this study, it was shown that the adverse emotions in the observation group were lower than those in the control group, which indicated that standardized care could effectively reduce the adverse emotions of patients and was effective.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, none of this clinical leadership is possible without collaboration with educational, research, policy and executive leaders who know how to work together to achieve these bold ambitions. Our clinical, executive, educational and research leaders have described the innovations in collaborative practice (Gronkjaer et al, 2022) that will enable such ambitions to come to be realized.…”
mentioning
confidence: 99%
“…Of course, none of this clinical leadership is possible without collaboration with educational, research, policy and executive leaders who know how to work together to achieve these bold ambitions. Our clinical, executive, educational and research leaders have described the innovations in collaborative practice (Gronkjaer et al, 2022) that will enable such ambitions to come to be realized.…”
mentioning
confidence: 99%